Phase coexistence in Bi1-xPrxFeO3 ceramics - Karpinsky, D. V.
Bi1-x Pr (x) FeO3 ceramics across the rhombohedral-orthorhombic phase boundary have been studied by X-ray diffraction, transmission electron microscopy, and differential scanning calorimetry. The structural phase transitions in Bi1-x Pr (x) FeO3 driven by doping concentration and temperature are significantly different from those in BiFeO3 compounds doped with other rare-earth elements. The features of the structural transformations have been discussed based on the specific character of the chemical bonds associated with praseodymium ions. The detailed study of the crystal structure evolution clarified the ranges of both single-phase and phase coexistence regions at different temperatures and dopant concentrations. For x = 0.125, compound extraordinary three-phase coexistence state has been observed in a narrow temperature range at about 400 A degrees C. The results explicate driving forces of the structural transitions and elucidate the origin of the remarkable physical properties of BiFeO3-based compounds near the morphotropic phase boundary.